Ethnomathematics-Based Geometry Framework to Improve Students Metacognitive Skills and Mathematical Understanding - Ni Kadek Dwi Paramitha; I Made Suarjana; I Nyoman Laba Jayanta (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Mathematics is often considered difficult because the material is abstract, so the learning process requires media to help students understand concepts more concretely. This study aims to produce an ethnomathematics-based geometry framework with valid, practical, and effective criteria. The type of research used is development research with the ADDIE model. The test subjects involved material and media experts and 32 fifth-grade elementary school students. Data was collected through questionnaires and tests using instruments like questionnaire sheets and test questions. The data obtained were analyzed using qualitative and quantitative descriptive analysis methods. The results showed that the developed framework obtained a decent assessment from material experts, media experts, and small groups of students. In addition, the results of the effectiveness test through hypothesis analysis showed a significant difference between students' metacognitive abilities and mathematical understanding before and after using the media. This indicates that the framework developed is valid, feasible to use, and effective in improving the quality of mathematics learning, especially in geometry materials. This research implies that teachers can utilize the ethnomathematics-based geometry framework as a contextual learning tool, and by the characteristics of students in understanding geometry concepts in grade V elementary school.